Pengukuran Kinerja Yayasan Unit Air Bersih Nagari Gurun Menggunakan Metode Balanced Scorecard - Rahmi, Mega; Yusri, Misbah; Hamdani, Muchlas; Hakim, Muhammad Irfanul; Fikri, Nurul; Putra, Yosep Eka (Journal of Economics and Management, 2024)
The purpose of this paper is to analyze performance measurements at the Desert Development Drive Foundation for clean water units using the Balance Scorecard method. A Balanced Scorecard is a framework that helps organizations plan, focus, and manage their strategy. Located in Nagari Gurun, Sungai Tarab sub-district. This type of research includes quantitative data. and There were four discussions about performance during this study. First, financial effectiveness. Second, customer effectiveness, including target market, services, and ways to get more customers. Third, effective business processes and business rules. Fourth, effective expansion and innovation of clean water in Nagari Gurun. This study found that implementing BSC increases employees' understanding of the company's strategic goals, improves the way managers communicate with customers, and increases customer satisfaction. Additionally, the study found that BSC helps management make better and more conscious decisions. These results demonstrate the importance of BSC as a tool for achieving competitive advantage in a dynamic business environment, as well as contributing to management practices. It is hoped that this research can help the Nagari Gurun Clean Water Unit Foundation in measuring the performance carried out in the decision-making process and innovation for the future.